Microbiomes of Muricea californica and M. fruticosa: Comparative Analyses of Two Co-occurring Eastern Pacific Octocorals - Holm, Johanna B.; Heidelberg, Karla B. (Frontiers in Microbiology, 2016)
Octocorals are sources of novel, but understudied microbial diversity. Conversely, scleractinian or reef-building coral microbiomes have been heavily examined in light of the threats of climate change. Muricea californica and Muricea fruticosa are two co-occurring species of gorgonian octocoral abundantly found in the kelp forests of southern California, and thus provide an excellent basis to determine if octocoral microbiomes are host-specific. Using Illumina MiSeq amplicon sequencing and replicate samples, we evaluate the microbiomes collected from multiple colonies of both species of Muricea to measure both inter- and intra-colony microbiome variability. In addition, microbiomes from overlying seawater and nearby zoanthids (another benthic invertebrate) were also included in the analysis to evaluate whether bacterial taxa specifically associate with octocorals. This is also the first report of microbiomes from these species of Muricea. We show that microbiomes isolated from each sample type are distinct, and specifically, that octocoral species type had the greatest effect on predicting the composition of the Muricea microbiome. Bacterial taxa contributing to compositional differences include distinct strains of Mycoplasma associated with either M. californica or M. fruticosa, an abundance of Spirochaetes observed on M. californica, and a greater diversity of γ-Proteobacteria associated with M. fruticosa. Many of the bacterial taxa contributing to these differences are known for their presence in photosymbiont-containing invertebrate microbiomes.